Modifiers of position-effect variegation in the region from 86C to 88B of the Drosophila melanogaster third chromosome. - Reuter, G.; Gausz, J.; Gyurkovics, H.; Friede, B.; Bang, R.; Spierer, A.; Hall, L.M.C.; Spierer, P. (Molecular and General Genetics, 1987)
Four dominant suppressor and one enhancer of variegation loci were mapped in the polytene chromosome region extending from section 86C to section 88B of the Drosophila melanogaster third chromosome using a set of deficiencies. The suppressor locus Su-var(3)14 maps in 86CD, Su-var(3)13 in 86F4-7, Su-var(3)6 in 87B4-7 and Su-var(3)7 in 87E4-5. The enhancer locus E-var(3)3 maps in 87E12-F11. Su-var(3)13, Su-var(3)6 and Su-var(3)7 are also defined by point mutant alleles originally identified by other criteria (Reuter et al. 1986). Duplications covering the suppressor loci Su-var(3)14, Su-var(3)13, Su-var(3)6 and Su-var(3)7 were found to reduce considerably the haplo-abnormal effect of heterozygous point mutants of the corresponding loci. One suppressor locus, Su-var(3)7, maps within a region which has previously been cloned. The positions of deficiency breakpoints delimiting the suppressor locus indicate that all the necessary sequences for its function are located within 10 kb of cloned DNA.